Pengembangan Modul Pembelajaran dengan Pendekatan Realistic Mathematics Education (RME) pada Materi Bangun Ruang Sisi Datar - Bahar, Miftahul Jannah Aprilia; Majid, Ahmad Farham; Yuliany, Nur; Munirah; Sriyanti, A. (Faculty of Tarbiyah and Teacher Training, 2024)
This study aims to determine the process of developing learning modules with the RME approach and the validity, practicality, and effectiveness in improving student learning outcomes through learning modules with the RME approach. The type of research used is Research and Development (R&D), and it concerns the ADDIE development module, namely Analysis, Design, Development, Implementation, and Evaluation. The trial subjects in this study were 31 students of class VIII A of SMPN 2 Bontonompo Selatan. The instruments used in this study were expert validation sheets (media and materials), teacher response questionnaires, student response questionnaires, observation sheets of teacher abilities in managing learning, observation sheets of student activities, and learning outcome tests. Based on the study's results, it was found that the learning module with the RME approach met the criteria of being valid, practical, and effective. Thus, it can be concluded that the learning module with the RME approach is feasible for learning and can be an innovative alternative in improving the quality of mathematics learning that is more effective, practical, and according to student needs.